Sleep Disorders Among Students of Baquba Technical Institute - Amer Abd Al gabar, Fatima; Jabbar Abdu-alkadhm, Salam; Sattar Awad, Hiba (Futurity Medicine, 2025)
The descriptive study was conducted at the Technical Institute in Baquba from 14/2/2024 to 20/3/2024, to identify sleep disorders among students of the Technical Institute. A non-probability sample was selected for a purposive sample consisting of (100) male and female students. A knowledge-monitoring questionnaire was used to collect students' data, comprising two sections. The first section covered the students' demographic information, and the second section examined the axes of sleep disorders. The Statistical Program for Social Sciences, version 20, was used to analyse the collected data using descriptive and inferential statistics. The test results revealed that most students suffer from sleep disorders. The study concluded that there is no statistically significant relationship between the effectiveness of guidance programs, years of experience, educational level, number of caregiver training courses, and the occurrence of emergency cases at the P≤0.05 significance level. The study recommended the need to conduct research on a broader scale for students of different universities due to its importance on the students' academic performance. The study recommends ​​including the research topic in the vocabulary of scientific curricula.